WAYS TO STRENGTHEN INVESTMENT ACTIVITY IN UZBEKISTAN THROUGH THE DEVELOPMENT OF THE CAPITAL MARKET - Tirkashev Farruxjon Khоlyigitovich (The Conference Hub, 2025)
Today, the capital market is recognized as a crucial tool for economic growth in countries around the world. The capital market plays a fundamental role in the efficient allocation of financial resources, attracting long-term investments for businesses, and creating investment opportunities for investors. Countries with well-developed capital markets globally achieve high rates of economic growth, foster innovation, and attract foreign investments. Therefore, improving and expanding the capital market is of strategic importance for every country.